Development and Performance Evaluation of an Instrumented Hybrid Onion Storage Facility - Babatunde Soyoye; Ademola Okunjoyo; Adenike Aderotoye (ABUAD Journal of Engineering Research and Development)
Onion (Allium cepa L.) is one of the oldest bulb crops, known to mankind and consumed worldwide. It is valued for its distinct pungent flavour and is an essential ingredient for the cuisine of many regions. This study aimed to develop and evaluate the performance of a refrigerated onion storage facility. The designed facility was simple, efficient, and cost-effective, with a focus on user-friendly operation and packaging of onions in zippered bags. The experiment involved slicing and dicing onions of equal size, which were then placed in zip bags and monitored over a week. The mass of the samples was measured daily to observe the changes. Additionally, laboratory analysis was conducted to assess the proximate composition, phytochemical contents, and heavy metal concentration of the onions. The results showed that the storage facility maintained a cooling rate of 0oC and experienced fluctuations in temperature due to external weather conditions. The relative humidity ranged from 18% to 19%, indicating the coldness of the storage facility. The analysis of the onion samples revealed high moisture content, with values ranging from 80% to 90%. Other compositional parameters such as crude protein, CHO, crude fibre, fat content, and ash content were relatively low. In terms of phytochemical analysis, flavonoid content was found to be relatively high compared to saponin, alkaloid, and tannin contents. Flavonoid content was highest in the raw state of the onion. Heavy metal analysis showed significant differences in the concentrations of iron (Fe), manganese (Mn), and zinc (Zn), while copper (Cu) did not exhibit a significant effect. The developed refrigerated onion storage facility demonstrated promising performance. The proximate composition analysis indicated that before and after storage of the onions, the moisture content and nutrients of onions was maintained. The phytochemical analysis revealed a significant presence of flavonoids, while heavy metal analysis showed varying concentrations of Fe, Mn, Zn, and Cu.